Toward a Research Roadmap for Construction Mediation - İlter, Deniz; Irlayıcı Çakmak, Pınar; Arıcı Üstüner, Yaprak; Taş, Elçin (Emerald Publishing, 2016)
Purpose – This paper aims to outline the state-of-the-art and research contributions in the construction mediation domain to determine whether existing research is compatible with a future scenario envisioning a wider adoption and more systemised use of mediation in the construction industry and to develop a research agenda based on key challenges facing mediation. Design/methodology/approach – A systematic procedure based on keywords was adopted for the selection of relevant research contributions in the area, and a meta-classification framework has been designed based on independent classifications of the content, method and authorship to analyse the publications. Findings – Research contributions in the past decade mostly focused on perceptions of professionals on mediation and the dynamics of the mediation process and mediator tactics. Based on the challenges identified, proposed research agenda includes court-connected mediation, mediation in public projects, project mediation, documentation of case studies of mediation applications and use of IT in mediation. Research limitations/implications – The publications investigated in this study are limited to scholarly articles published in the mainstream construction management journals and can be expanded to books or articles published in law journals if required. Originality/value – Existing literature includes important contributions regarding many aspects of construction mediation, however, a holistic agenda is lacking to overcome the key challenges to the widespread use of mediation in the construction sector. The research directions presented in this paper is expected to contribute to the proliferation of the neglected areas and constitute the basis for the development of a research roadmap in the construction mediation domain.
Keywords: Literature Review; Construction Industry; Research Agenda; Mediation; Alternative Dispute Resolution; Research Roadmap